Stress analysis of the piston due to heat transfer using finite element analysis (FEA) Software / Mohd. Zulkifli Salleh - Salleh, Mohd. Zulkifli (2005)
This final project is a study about the stress analysis of the piston due to the heat transfer. This project consist of the heat engine process, stress analysis, study the software for simulation purpose, simulation of the piston model and finally get the results from the simulation. The Finite Element Analysis (FEA) Nastran software is used to simulate the stress on entire of the piston model in the internal combustion chamber. The model of the piston is constructing in the CATIA V 5 software and then the simulation was done in Finite Element Analysis (FEA) Nastran software. From the results of the simulation, the stress distribution and the critical area was acting on the piston model when the heat flux was applied to the piston can be analyzed. All of the description and result of the research are included in this thesis. The finding of this project is that the aluminium alloy used to employ on the piston had lower stress distribution due to the higher heat dissipation compare to the cast iron. It is hoped that this research can produce some relevant basic information and benefit to any parties who would like to further it.